Metode Praktis Menentukan Arah Kiblat dan Koreksi Arah Kiblat - Mikrajuddin Abdullah (State Institute of Islamic Studies (IAIN) Tulungagung, 2017)
This paper explains a simple method used to determine the direction of Qibla or do the correction of Qibla direction in the mosque, mushola, or surau that already exist. The proposed method only utilizes the GoogleMap facility provided by Google. The approach is taken to draw a straight line from Ka'bah to the location where the mosque will be built. This Method is interesting to teach in Islamic high schools or Islamic education programs in colleges.